(untitled) (Semiárida, 2020)
The aim of this experiment was to compare dry matter (DM) production rates and nutritive value of a warm-season grass, Digitaria erisntha ev. Irene, in two locations of Central Argentina, Santa Rosa (SR) and Villa Mercedes (VM). The plants were established in two identical groups of plots, within a randomized block design DM rates were calculated from serial, out of phase clippings, and in vitro dry matter digestibility (IVDMD) and crude protein (CP) content analyzed on subsamples. The study lasted for three consecutive growing seasons. Results showed that DM production rates were generally higher (P<0.05) in SR than in VM, but IVDMD and CP content showed no clear trends between both locations. DM production tended to lower from year 1 to 3, related to processes of N depletion from soils (VM) and diminishing rainfall (SR). It is concluded that D. eriantha is a very promising warm-season grass to Central Argentina. Data of nutritive value obtained in one location can be used in others, but results of DM production rates should be taken under the conditions where they will be used. Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.) Publicado en Proceedings of the XVIII international grassland congress. Forage and Management, Session 22: 101-102, 1997.